Editorial Perspective: Longitudinal research in autism – introducing the concept of 'chronogeneity'. (May 2017) - Georgiades, Stelios; Bishop, Somer L.; Frazier, Thomas
Abstract: Autism Spectrum Disorder (ASD or autism) is a heterogeneous neurodevelopmental disorder. We are now at a critical juncture in autism research where we have the knowledge base and expertise to begin to think about studies that view heterogeneity, not as 'statistical noise' that can be 'accounted for' using data‐reduction techniques (such as group trajectories), but rather as 'informative variance' that can help form a more precise and dynamic picture of autism. In this Editorial we coin a new term and introduce the concept of 'chronogeneity' for the study of autism heterogeneity in relation to the dimension of time (chrono). Using examples of ongoing research and analytical advances we build the case for the potential utility of the concept of 'chronogeneity' and argue that a refined approach to the longitudinal investigation of autism (and other neurodevelopmental disorders) may move us closer to more precise and adaptive models of care for the children and youth affected by these disorders.